UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAN FRAKSI ETIL ASETAT DARI EKSTRAK DAUN JARAK PAGAR (JATROPHA CURCAS L.) TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS - Dewi, Hasna (Journal of Pharmacy Tiara Bunda, 2023)
Staphylococcus Aureus is a gram-positive bacteria that can cause infection. One of the plants that has antibacterial activity is jatropha leaves which contain flavonoids, saponins, tannins, alkaloids, steroids, and polyphenols. This study aims to determine the antibacterial activity of ethanol extract and ethyl acetate fraction with concentrations of 30%, 60% and 100% against staphylococcus aureus bacteria. The method for extracting jatropha leaves is maceration with 96% ethanol solvent and the fractionation method, namely liquid-liquid fractionation with ethyl acetate solvent. Antibacterial activity test was carried out in vitro with the disc diffusion method and compared the mean zone of inhibition of each treatment with a positive control (gentamicin 10 µg). The results showed that the ethanol extract and ethyl acetate fraction of jatropha leaves had a strong resistance response, while the positive control gave a very strong inhibitory response to the growth of staphylococcus aureu bacteria. Based on the one way ANOVA test, ethanol extract and ethyl acetate fraction showed a significant difference from each treatment (P = ˂0.05). The conclusion of this study is that the ethanol extract of Jatropha leaves can inhibit the growth of staphylococcus aureus bacteria at a concentration of 100% (18.28 ± 0.50mm), 100% concentration of ethyl acetate fraction (15.10 ± 0.12mm). The ethanol extract provided the best inhibition power, namely 18.28 ± 0.50mm and a positive control 21.82 ± 0.092mm